Genetic Regulation of Fibroblast Activation and Proliferation in Cardiac Fibrosis. Issue 12 (18th September 2018) - Park, Shuin; Ranjbarvaziri, Sara; Lay, Fides D.; Zhao, Peng; Miller, Mark J.; Dhaliwal, Jasmeet S.; Huertas-Vazquez, Adriana; Wu, Xiuju; Qiao, Rong; Soffer, Justin M.; Rau, Christoph; Wang, Yibin; et al.
Abstract : Background: Genetic diversity and the heterogeneous nature of cardiac fibroblasts (CFbs) have hindered characterization of the molecular mechanisms that regulate cardiac fibrosis. The Hybrid Mouse Diversity Panel offers a valuable tool to examine genetically diverse cardiac fibroblasts and their role in fibrosis. Methods: Three strains of mice (C57BL/6J, C3H/HeJ, and KK/HlJ) were selected from the Hybrid Mouse Diversity Panel and treated with either isoproterenol (ISO) or saline by an intraperitoneally implanted osmotic pump. After 21 days, cardiac function and levels of fibrosis were measured by echocardiography and trichrome staining, respectively. Activation and proliferation of CFbs were measured by in vitro and in vivo assays under normal and injury conditions. RNA sequencing was done on isolated CFbs from each strain. Results were analyzed by Ingenuity Pathway Analysis and validated by reverse transcription-qPCR, immunohistochemistry, and ELISA. Results: ISO treatment in C57BL/6J, C3H/HeJ, and KK/HlJ mice resulted in minimal, moderate, and extensive levels of fibrosis, respectively (n=7–8 hearts per condition). Isolated CFbs treated with ISO exhibited strain-specific increases in the levels of activation but showed comparable levels of proliferation. Similar results were found in vivo, with fibroblast activation, and not proliferation, correlating with the differential levels of cardiac fibrosis after ISO treatment. RNA sequencing revealed that CFbs from each strain exhibit unique gene expression changes in response to ISO. We identified Ltbp2 as a commonly upregulated gene after ISO treatment. Expression of LTBP2 was elevated and specifically localized in the fibrotic regions of the myocardium after injury in mice and in human heart failure patients. Conclusions: This study highlights the importance of genetic variation in cardiac fibrosis by using multiple inbred mouse strains to characterize CFbs and their response to ISO treatment. Our data suggest that, although fibroblast activation is a response that parallels the extent of scar formation, proliferation may not necessarily correlate with levels of fibrosis. In addition, by comparing CFbs from multiple strains, we identified pathways as potential therapeutic targets and LTBP2 as a marker for fibrosis, with relevance to patients with underlying myocardial fibrosis. Abstract : Supplemental Digital Content is available in the text.